RETRACTED: Framework for Patient Safety - AK Mohiuddin (University of Minnesota Libraries Publishing, 2019)
This article has been retracted: please see INNOVATIONS in pharmacy retraction policy (https://pubs.lib.umn.edu/index.php/innovations/policies). This article has been retracted by the Editor and Publisher due to the inappropriate use of previously published work. A commitment on quality objectives is a crucial element of quality policy in HROs, such as hospitals and other healthcare institutions. The quality of care includes objectives related to effectiveness, efficiency, and a patient's experience. Healthcare organizations are also aware of the importance of promoting safety practices and the resiliency analysis of the clinical practice in order to improve quality. Patient Safety Culture has been defined as the product of individual and group values, attitudes, competencies, and patterns of behavior that determines their commitment, style, and proficiency with the organization's health and safety programs. The safety culture of a health center offers an indirect means for its involvement in quality. Poor involvement of professionals in safety has negative consequences for patients. Envisioning the future of patient safety is more than an academic exercise. Appealing visions can help channel human energies, set new directions, and open the doors to alternative approaches. An outside observer is struck by three characteristics that are very different from the culture of the early 21st century: a deep sense of individual and institutional accountability for safety, an emphasis on fairness and transparency, and pervasive collaboration and teamwork based on mutual respect. Speaking up is important for patient safety, but healthcare professionals often hesitate to voice their concerns. Direct supervisors have an important role in influencing speaking up. However, good insight into the relationship between managers' behavior and employees' perceptions about whether speaking up is safe and worthwhile is still lacking. The evaluation should cover the following areas in both instruments: strategy (inquiry on their commitment to the quality and safety strategy, indicators' feedback, and risks maps), support systems for clinical decisions (digital record algorithms to make decisions and for accessibility to patient clinical information), equipment (adequacy), follow-up (availability of tests when needed), person-centered care (respect of patients' values and preferences), evidence-based practice (practices in accordance with guidelines), delays (on scheduled tests, surgery, and outpatient care), and cost-effective treatments (adequacy).   Article Type: Commentary